Rapid Lithium Diffusion in Order@Disorder Pathways for Fast‐Charging Graphite Anodes - Cai, Wenlong; Yan, Chong; Yao, Yu-Xing; Xu, Lei; Xu, Rui; Jiang, Li-Li; Huang, Jia-Qi; Zhang, Qiang (Small structures, 2020)
The use of graphite anode renders practical lithium‐ion batteries for effective energy storage. However, graphite anode is the bottleneck to achieve the fast charging of a battery, ascribed to its low operating potential and corresponding incidental lithium plating. Herein the principle of a thin nanoscale layer on the graphite surface to improve charging capability is investigated by applying a three‐electrode device to precisely record the working behavior. The Li+ diffusion rate is significantly improved by coating a nanoscale turbostratic carbon layer, in which abundant active sites and additional fast Li+ diffusion pathways at the basal‐plane side of graphite sheets render small polarization in a working battery. This fresh understanding enriches the fundamental insights into enhancing the rate performance and facilitating the practical applications of graphite in fast‐charging batteries. The turbostratic carbon layer on the graphite anode affords abundant active sites and fast diffusion pathways to accelerate the transportation of Li ions in a working battery. This renders a reduced polarization and significantly improved rate performance.